Legal Protection for Workers Related to Layoff Cases Linked to Law Number 6 of 2023 Concerning Job Creation (Study of Supreme Court Decision Number 600 K/Pdt.Sus-Phi/2024) - Putra, Affian Fandi; Abas, M; Rahmatiar, Yuniar (DE LEGA LATA: JURNAL ILMU HUKUM, 2025)
Layoffs can be defined as a permanent stop of work between the Company and workers/laborers, or when workers leave the Company that employs them, this research focuses on revealing how worker protection after the enactment of Law Number 6 of 2023 concerning Job Creation, as well as how the judge's consideration in deciding case number 600 K/Pdt.Sus-Phi/2024 in layoff cases. The research method is normative juridical sourced through primary, secondary, and tertiary legal materials, the main object of which is the Supreme Court's decision number 600 K/Pdt.Sus-Phi/2024, which is used to analyze the judges' considerations in layoff cases after the enactment of Law Number 6 of 2023 concerning Job Creation which rearranges the layoff mechanism by emphasizing legal protection, fair compensation, and social security for workers, but still leaves challenges in implementation and legal certainty, the Supreme Court stated that the layoff of Serefina L. Tobing must be qualified as a layoff. Tobing must be qualified as early retirement, and determine compensation in accordance with the provisions of article 56 of Government Regulation Number 35 of 2021, so that the Company is required to pay workers' normative rights fairly. Layoffs in the Indonesian labor system are still a complex problem and require fair legal arrangements. law number 6 of 2023 concerning job creation significantly changes the structure and mechanism of layoffs, the consideration of judges both at the first and cassation levels, has been carried out carefully, and in accordance with the principles of justice and applicable legal provisions. The Panel of Judges considered that Serefina L. Tobing met the requirements for early retirement as stipulated in the PKB and Government Regulation No. 35 of 2021.